Evaluation of pulsed electromagnetic field protocols in implant osseointegration: in vivo and in vitro study - Nunes, Camilla Magnoni Moretto [UNESP]; Ferreira, Camila Lopes [UNESP]; Bernardo, Daniella Vicensotto [UNESP]; Lopes, Cássia Carolina Rabelo [UNESP]; Collino, Luma [UNESP]; da Silva Lima, Victória Clara [UNESP]; de Camargo Reis Mello, Daphne [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (Springer Nature, 2021)
Objectives: The present study aims to evaluate two protocols of pulsed electromagnetic field (PEMF) on osseointegration and establish one that addresses ideal parameters for its use in dentistry, especially in the optimization of the implants osseointegration process. Materials and methods: Sixty male rats (Wistar) were allocated into three experimental groups: control (GC), test A (GTA, 3 h exposed), and test B (GTB, 1 h exposed). All animals received titanium implants in both tibias, and PEMF application (15 Hz, ± 1 mT, 5 days/week) occurred only in the test groups. They were euthanized at 03, 07, 21, and 45 days after PEMF therapy. Removal torque, histomorphometric measurements, three-dimensional radiographic evaluation, and in vitro biological assay analyses were performed. Results: GTB showed better results compared with GTA in removal torque tests, in bone volume and bone mineral density, cell viability, total protein content, and mineralization nodules (p < 0.05). GTA showed better performance in trabecular bone thickness and cell proliferation compared with GTB (p < 0.05), especially at osseointegration early periods. In the histomorphometric analysis and number of trabeculae, there were no differences in the test groups. Conclusion: PEMF as a biostimulator was effective in optimizing the events in bone tissue that lead to osseointegration, especially when applied for a shorter time and in the initial periods of bone healing. Clinical relevance: The PEMF therapy is an effective alternative method for optimizing bone healing.
Keywords: Bone-anchored implants; Electromagnetic fields; Osseointegration; Rats